Analysis of the symmetric configuration of the circle of Willis in a series of autopsied corpses - Stojanović, Nebojša N; Stefanović, Ivica; Kostić, Aleksandar; Mitić, Radisav; Radisavljević, Miša; Stojanov, Dragan; Petrović, Sladjana (Vojnosanitetski pregled, 2015)
Introduction. The forming of the blood vessels network configuration at the base of the brain and interconnecting of blood vessels during the embryogenesis is directly related to the phylogenetic development of the brain and brain structures. A blood vessel configuration at the brain base, in the form of a ring or a hexagon, stands in direct relation to the perfusion needs of certain parts of the brain during its primary differentiation. The aim of this paper was to determine the incidence of certain blood vessel configurations at the base of the brain and understanding their symmetry or asymmetry. Methods. Analysis of the blood vessels at the base of the brain was performed on the autopsied subjects. The object of observation was the anterior segment of the circle of Willis consisting of C1- a. carotis interna (ICA), above a. communicaus posterior (PcoA), the segment A1 a. cerebri anterior (ACA) from a. carotis interna bifurcation to the a. communicans anterior (AcoA) and a. communicans anterior itself, as well as the posterior segment consisting of PcoA and the segment P1 – a. cerebri posterior (PCA) from the a. basilaris bifurcation to the PcoA. For the purpose of grouping the findings, the four basic configuration types of the circle of Willis were identified based on its symmetry or asymmetry. Type-A (symmetric circle of Willis), type-B (asymmetric circle of Willis’ due to the unilateral hypoplastic A1-ACA); type-C (symmetric circle of Willis with bilateral symmetric changes on PcoA) and type-D (asymmetric circle of Willis due to the asymmetric changes on PcoA). Results. Autopsy was performed on 56 corpses. A total of 41 (73.2%) subjects were recorded with a symmetric configuration of the circle of Willis’, of which 27 (48.2%) subjects had type A and 14 (25%) type C. The asymmetric configuration was present in 15 (26.8%) subjects, of whom 9 (16%) had type B and 6 (10.8%) type D. The symmetric Willis group (73.2%) did not have a homogeneous finding that would fit into the schematic presentation of the symmetric type A and type C. A total of 17 (30.4%) findings were classified in this group of the so-called conditionally symmetric configurations. In all the cases, type B (16%) had unilaterally reduced diameter A1 and hyperplastic AcoA. Conclusion. The presence of asymmetric Willis configuration in 26.8% of the cases, which makes up more than one fourth, indicates that the asymmetric configurations do not represent a pathological form of connecting the blood vessels at the base of the brain, but rather one aspect of its adaptation. The forming of the basic types of configurations of the circle of Willis is associated with a tendency toward certain types of hemodynamic disorders and more frequent pathological changes in places of reduced resistance.